A Survey of Recent Results for the Generalizations of Ordinary Differential Equations - Daniel C. Biles; Márcia Federson; Rodrigo López Pouso (Abstract and Applied Analysis)
This is a review paper on recent results for different types of generalized ordinary differential equations. Its scope ranges from discontinuous equations to equations on time scales. We also discuss their relation with inclusion and highlight the use of generalized integration to unify many of them under one single formulation.